1993
DOI: 10.1172/jci116852
|View full text |Cite
|
Sign up to set email alerts
|

Low protein diet alters urea transport and cell structure in rat initial inner medullary collecting duct.

Abstract: Low protein diets reverse the urea concentration gradient in the renal inner medulla. To investigate the mechanism(s) for this change, we studied urea transport and cell ultrastructure in initial and terminal inner medullary collecting ducts (IMCD) from rats fed 18% protein or an isocaloric, 8% protein diet for 4 wk. Serum urea, aldosterone, and albumin were significantly lower in rats fed 8% protein, but total protein and potassium were unchanged. Vasopressin stimulated passive urea permeability (P.") threefo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
61
0

Year Published

1998
1998
2020
2020

Publication Types

Select...
3
3
2

Relationship

1
7

Authors

Journals

citations
Cited by 52 publications
(69 citation statements)
references
References 39 publications
8
61
0
Order By: Relevance
“…No significant difference was found between DM and CO rat mellitus is different because the changes in UT mRNA and protein abundance observed in diabetes mellitus differ from those resulting from protein-rich diet (unchanged mRNA [40], and decreased 117000 M r isoform [31]). In contrast, some of the diabetes-induced changes resemble those induced by chronic low protein feeding, such as extension of UT-A1 mRNA [41] and vasopressin-dependent urea permeability [33,42] to the initial part of the IMCD, increase in the 117000 M r isoform [31], and lack of change in UT-A2 and UT-B1 mRNA abundance [40].…”
Section: Discussionmentioning
confidence: 96%
“…No significant difference was found between DM and CO rat mellitus is different because the changes in UT mRNA and protein abundance observed in diabetes mellitus differ from those resulting from protein-rich diet (unchanged mRNA [40], and decreased 117000 M r isoform [31]). In contrast, some of the diabetes-induced changes resemble those induced by chronic low protein feeding, such as extension of UT-A1 mRNA [41] and vasopressin-dependent urea permeability [33,42] to the initial part of the IMCD, increase in the 117000 M r isoform [31], and lack of change in UT-A2 and UT-B1 mRNA abundance [40].…”
Section: Discussionmentioning
confidence: 96%
“…Schmidt-Nielsen and colleagues first demonstrated the existence of active urea reabsorption which is coupled to sodium reabsorption in the kidney of the spiny dogfish, Squalus acanthias (16). We showed that urea is actively reabsorbed via a secondary active, sodium-coupled cotransport process in the rat initial IMCD (IMCD 1 ) from rats fed a low-protein diet for 3 wk (9)(10)(11). We also showed that urea is actively secreted via a secondary active, sodium-coupled countertransport process in the deepest portion of the rat terminal IMCD, the IMCD 3 , but not in the middle third of the IMCD, the IMCD 2 , nor in the initial IMCD of rats fed a normal diet (12).…”
Section: Introductionmentioning
confidence: 91%
“…To study active urea transport, tubules were perfused with the same perfusate and bath solution (except during the ion substitution studies described below) whose composition was identical to the dissection solution (described above) except that 3 mM urea was added to the solution (9,10,12). To calculate J urea , V o is assumed to be equal to V l , because there is no osmotic gradient across the tubule and hence, no driving force for water reabsorption.…”
Section: Protocolsmentioning
confidence: 99%
See 1 more Smart Citation
“…UT-A) and secondary active Na + /urea counter-transport systems (Chou and Knepper, 1989;Isozaki et al, 1993;Isozaki et al, 1994a;Isozaki et al, 1994b;Sands et al, 1996;Kato and Sands, 1998a;Kato and Sands, 1998b), but not Na + /urea cotransporters, and because water with a salinity of 1 contained ~15mmoll -1 Na + , which was higher than the normal intracellular Na + concentration (10mmoll -1 ), the possibility of a Na + /urea counter-transporter being expressed in the apical membrane of the buccopharyngeal epithelial cells of P. sinensis cannot be eliminated at present. However, active buccopharyngeal urea excretion resulted in extraordinarily high urea concentrations (~614mmoll -1 ) in the saliva of turtles injected intraperitoneally with urea; therefore, the possibility of the presence of a novel active urea transporter independent of Na + movement in the apical surface of the buccopharyngeal epithelium cannot be ignored.…”
Section: The Buccopharyngeal Epithelium Is Capable Of Active Urea Excmentioning
confidence: 97%